Pengaruh Inflasi dan BI Rate terhadap Indeks Harga Saham Gabungan (Studi Kasus pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2011-2015) - Maslikha, Henik; Puspitaningtyas, Zarah; Prakoso, Aryo (e-Sospol, 2017)
Abstract Investors in economic motive will afford to invest in stock of company that can provide profit and dividends. Capital market participants will observe the movement of the Composite Stock Price Index on the stock exchange as one of viewpoints to invest. Stock price index is influenced by several factors, such as inflation rate, interest rate, exchange rate. In analyzing theComposite Stock Price Index, the researcher only limited on the inflation and BI ratevariables. This research aims to know the effect of inflation and BI rate on Composite Stock Price Index (a case study on the property and real estate companies registered on the Indonesia Stock Exchange in period of 2011-2015). This research used a quantitative approach. 40 companies and real estate properties were taken as the samples which were obtained by using purposive sampling. Data were analyzed by using multiple linear regression method. The research results indicated that inflation did not affect the Composite Stock Price Index while BI rate significantly affected on the Composite Stock Price Index. Inflation and BI rate showed the result of 10.3% which means that the variation of inflation and BI rate variablesaffectedthe Composite Stock Price Index while the remaining of 89.7% was affected or caused by other factors that were not included in this research model.